Compound, molded body, and cured product of compound
A compound combining metal powder and a specific resin composition addresses the need for industrial products to balance strength and elastic modulus at high temperatures with excellent voltage resistance, achieving enhanced reliability.
Patent Information
- Application Number
- JP2021051746
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-25
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-03-25
AI Technical Summary
Industrial products such as inductors require a compound that balances strength and elastic modulus at high temperatures while also providing excellent voltage resistance.
A compound comprising a metal powder and a resin composition containing an epoxy resin, a hardener, a coupling agent with kinematic viscosity of 10 to 2000 mm at 25°C, and a multifunctional silane compound is used to form a molded body with improved mechanical properties and voltage resistance.
The compound achieves excellent flowability during molding and maintains superior mechanical properties and voltage resistance at high temperatures, enhancing the reliability of industrial products.
Smart Images

Figure 0007669749000001 
Figure 0007669749000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a compound, a molded article, and a cured product of the compound. [Background technology]
[0002] Compounds containing metal powders and resin compositions are used as raw materials for various industrial products depending on the physical properties of the metal powders. For example, compounds are used as raw materials for inductors, sealing materials, electromagnetic shields (EMI shields), bonded magnets, etc. (see Patent Document 1 below). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-13803 A Summary of the Invention [Problem to be solved by the invention]
[0004] When an industrial product is manufactured from a compound, the compound and a metal member are adhered to each other, the compound is cured to produce a molded body, and the molded body is then heated. The molded body is required to have a good balance between strength and elastic modulus at high temperatures and to improve reliability. In addition, industrial products such as inductors may be required to have resistance to voltage.
[0005] The present invention aims to provide a compound capable of forming a molded article having an excellent balance between strength and elastic modulus at high temperatures and excellent voltage resistance, a molded article using the compound, and a cured product of the compound. [Means for solving the problem]
[0006] A compound according to one aspect of the present invention comprises a metal powder, and a resin composition containing an epoxy resin, a curing agent, and a coupling agent, the coupling agent having a kinetic viscosity of 10 to 2000 mm at 25°C. 2 / s polyfunctional silane compound.
[0007] A molded article according to one aspect of the present invention includes the above-mentioned compound. A cured product according to one aspect of the present invention is a cured product of the above-mentioned compound. Effect of the Invention
[0008] According to the present invention, there are provided a compound capable of forming a molded article having excellent flowability during molding and excellent mechanical properties at high temperatures, a molded article using the compound, and a cured product of the compound. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Preferred embodiments of the present invention will be described below, however, the present invention is not limited to the following embodiments.
[0010] [Compound] The compound according to the present embodiment includes a metal powder and a resin composition. The metal powder may contain at least one selected from the group consisting of a simple metal, an alloy, an amorphous powder, and a metal compound. The resin composition contains at least an epoxy resin, a curing agent, and a coupling agent. The coupling agent has a kinetic viscosity of 10 to 2000 mm at 25°C. 2The compound includes a polyfunctional silane compound having a structure of / s. In the compound, the metal powder, the epoxy resin, the curing agent, and the coupling agent are mixed. The resin composition may further contain a curing accelerator, a release agent, an additive, and the like as other components. The resin composition may be a component that may include the epoxy resin, the curing agent, the coupling agent, the curing accelerator, the release agent, and the additive, and may be the remaining components (non-volatile components) excluding the organic solvent and the metal powder. The additive is the remaining component of the resin composition excluding the resin, the release agent, the curing agent, the curing accelerator, and the coupling agent. The additive is, for example, a flame retardant, a lubricant, and the like. The compound may be a powder (compound powder).
[0011] The compound may comprise a metal powder and a resin composition attached to the surface of each metal particle constituting the metal powder. The resin composition may cover the entire surface of the particle, or may cover only a part of the surface of the particle. The compound may comprise an uncured resin composition and a metal powder. The compound may comprise a semi-cured product of the resin composition (e.g., a B-stage resin composition) and a metal powder. The compound may comprise both an uncured resin composition and a semi-cured product of the resin composition. The compound may be composed of a metal powder and a resin composition.
[0012] The content of the metal powder in the compound is preferably 90% by mass or more and less than 100% by mass with respect to the total mass of the compound. If the content of the metal powder is high, it is difficult to ensure the releasability of the molded body, and the workability tends to be poor. From the viewpoint of the magnetic properties of the molded body, the content of the metal powder is preferably 92% by mass or more, more preferably 94% by mass or more, and even more preferably 95% by mass or more. The upper limit of the content of the metal powder may be 99% by mass or less, 98% by mass or less, or 97.5% by mass or less.
[0013] (Resin composition) The resin composition functions as a binder for the metal particles that constitute the metal powder, and imparts mechanical strength to a molded body formed from the compound. For example, the resin composition contained in the compound fills between the metal particles when the compound is molded under high pressure using a mold, and binds the particles together. By curing the resin composition in the molded body, the cured resin composition binds the metal particles together more firmly, improving the mechanical strength of the molded body.
[0014] The resin composition according to the present embodiment contains an epoxy resin as a thermosetting resin, thereby improving the fluidity of the compound. The epoxy resin may be, for example, a resin having two or more epoxy groups in one molecule. The type of epoxy resin is not particularly limited and can be selected according to the desired properties of the resin composition.
[0015] Examples of epoxy resins include biphenyl type epoxy resins, stilbene type epoxy resins, diphenylmethane type epoxy resins, sulfur atom-containing epoxy resins, novolac type epoxy resins, dicyclopentadiene type epoxy resins, salicylaldehyde type epoxy resins, copolymer type epoxy resins of naphthols and phenols, epoxidized products of aralkyl type phenolic resins, bisphenol type epoxy resins, epoxy resins containing a bisphenol skeleton, glycidyl ether type epoxy resins of alcohols, glycidyl ether type epoxy resins of paraxylylene and / or metaxylylene modified phenolic resins, terpene modified phenolic resins, and the like. Examples of the epoxy resins include glycidyl ether type epoxy resins of phenol resins, cyclopentadiene type epoxy resins, glycidyl ether type epoxy resins of polycyclic aromatic ring-modified phenol resins, glycidyl ether type epoxy resins of naphthalene ring-containing phenol resins, glycidyl ester type epoxy resins, glycidyl type or methylglycidyl type epoxy resins, alicyclic type epoxy resins, halogenated phenol novolac type epoxy resins, ortho-cresol novolac type epoxy resins, hydroquinone type epoxy resins, trimethylolpropane type epoxy resins, and linear aliphatic epoxy resins obtained by oxidizing olefin bonds with a peracid such as peracetic acid.
[0016] In terms of fluidity, the epoxy resin may include at least one selected from the group consisting of biphenyl type epoxy resins, orthocresol novolac type epoxy resins, phenol novolac type epoxy resins, bisphenol type epoxy resins, epoxy resins having a bisphenol skeleton, salicylaldehyde novolac type epoxy resins, and naphthol novolac type epoxy resins.
[0017] In terms of mechanical strength, the epoxy resin may contain at least one selected from the group consisting of biphenylene aralkyl type epoxy resins and orthocresol novolac type epoxy resins.
[0018] The epoxy resin may be a crystalline epoxy resin. Although the molecular weight of the crystalline epoxy resin is relatively low, the crystalline epoxy resin has a relatively high melting point and is excellent in fluidity. The crystalline epoxy resin (highly crystalline epoxy resin) may include at least one selected from the group consisting of hydroquinone type epoxy resin, bisphenol type epoxy resin, thioether type epoxy resin, and biphenyl type epoxy resin.
[0019] Commercially available crystalline epoxy resins include, for example, Epicron 860, Epicron 1050, Epicron 1055, Epicron 2050, Epicron 3050, Epicron 4050, Epicron 7050, Epicron HM-091, Epicron HM-101, Epicron N-730A, Epicron N-740, Epicron N-770, Epicron N-775, Epicron N-865, Epicron HP-4032D, Epicron HP-7200L, Epicron HP-7200, Epicron HP-7200H, Epicron HP-7200HH, Epicron HP-7200HHH, Epicron HP-4700, Epicron HP-4710, Epicron HP-4770, Epicron HP-5000, Epicron HP-6000, N500P-2, and N500P-10 (product names manufactured by DIC Corporation); NC-3000, NC-3000-L, NC-3000-H, NC-310 0, CER-3000-L, NC-2000-L, XD-1000, NC-7000-L, NC-7300-L, EPPN-501H, EPPN-501HY, EPPN-50 2H, EOCN-1020, EOCN-102S, EOCN-103S, EOCN-104S, CER-1020, EPPN-201, BREN-S, and BREN-10S (all of which are trade names manufactured by Nippon Kayaku Co., Ltd.); YX-4000, YX-4000H, YL4121H, and YX-8800 (all of which are trade names manufactured by Mitsubishi Chemical Corporation).
[0020] The resin composition may contain one type of epoxy resin among the above. The resin composition may contain a plurality of types of epoxy resin among the above. Among the above epoxy resins, the resin composition may contain an epoxy resin containing a biphenyl skeleton, an orthocresol novolac type epoxy resin, or a multifunctional epoxy resin containing two or more epoxy groups.
[0021] Curing agents are classified into curing agents that cure epoxy resins in the range of low temperature to room temperature, and heat-curing type curing agents that cure epoxy resins by heating. Curing agents that cure epoxy resins in the range of low temperature to room temperature include, for example, aliphatic polyamines, polyaminoamides, and polymercaptans. Heat-curing type curing agents include, for example, aromatic polyamines, acid anhydrides, phenol novolac resins, and dicyandiamide (DICY). The type of curing agent is not particularly limited and can be selected according to the desired properties of the composition.
[0022] When a curing agent that cures an epoxy resin in the range of low temperature to room temperature is used, the glass transition point of the cured product of the epoxy resin is low, and the cured product of the epoxy resin tends to be soft. As a result, the molded product formed from the compound also tends to be soft. On the other hand, from the viewpoint of improving the heat resistance of the molded product, the curing agent may be preferably a heat-curing type curing agent, more preferably a phenolic resin, and even more preferably a phenolic novolac resin. In particular, by using a phenolic novolac resin as a curing agent, it is easy to obtain a cured product of an epoxy resin with a high glass transition point. As a result, the heat resistance and mechanical strength of the molded product are easily improved.
[0023] The phenolic resin may include at least one selected from the group consisting of, for example, aralkyl type phenolic resin, dicyclopentadiene type phenolic resin, salicylaldehyde type phenolic resin, novolac type phenolic resin, copolymer type phenolic resin of benzaldehyde type phenol and aralkyl type phenol, paraxylylene and / or metaxylylene modified phenolic resin, melamine modified phenolic resin, terpene modified phenolic resin, dicyclopentadiene type naphthol resin, cyclopentadiene modified phenolic resin, polycyclic aromatic ring modified phenolic resin, biphenyl type phenolic resin, and triphenylmethane type phenolic resin. The phenolic resin may be a copolymer composed of two or more of the above. As a commercially available phenolic resin, for example, Tamanoru 758 manufactured by Arakawa Chemical Industries Co., Ltd., or HP-850N manufactured by Hitachi Chemical Co., Ltd. may be used.
[0024] The phenol novolac resin may be, for example, a resin obtained by condensing or co-condensing phenols and / or naphthols with aldehydes under an acid catalyst. The phenols constituting the phenol novolac resin may include, for example, at least one selected from the group consisting of phenol, cresol, xylenol, resorcin, catechol, bisphenol A, bisphenol F, phenylphenol, and aminophenol. The naphthols constituting the phenol novolac resin may include, for example, at least one selected from the group consisting of α-naphthol, β-naphthol, and dihydroxynaphthalene. The aldehydes constituting the phenol novolac resin may include, for example, at least one selected from the group consisting of formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, and salicylaldehyde.
[0025] The curing agent may be, for example, a compound having two phenolic hydroxyl groups in one molecule. The compound having two phenolic hydroxyl groups in one molecule may include, for example, at least one selected from the group consisting of resorcin, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenol.
[0026] The resin composition may contain one type of phenolic resin from among the above. The resin composition may comprise a plurality of types of phenolic resins from among the above. The resin composition may contain one type of curing agent from among the above. The resin composition may contain a plurality of types of curing agents from among the above.
[0027] The ratio of the active group (phenolic OH group) in the curing agent that reacts with the epoxy group in the epoxy resin may be preferably 0.5 to 1.5 equivalents, more preferably 0.6 to 1.4 equivalents, and even more preferably 0.7 to 1.2 equivalents relative to 1 equivalent of the epoxy group in the epoxy resin. If the ratio of the active group in the curing agent is less than 0.5 equivalents, it is difficult to obtain a sufficient elastic modulus of the obtained cured product. On the other hand, if the ratio of the active group in the curing agent exceeds 1.5 equivalents, the mechanical strength of the molded product formed from the compound after curing tends to decrease. However, even if the ratio of the active group in the curing agent is outside the above range, the effect of the present invention can be obtained.
[0028] The coupling agent can improve the adhesion between the resin composition and the metal element-containing particles constituting the metal powder, and can improve the flexibility and mechanical strength of a molded body formed from the compound. The resin composition according to the present embodiment contains a coupling agent having a kinetic viscosity of 10 to 2000 mm at 25°C. 2 The resin composition contains a polyfunctional silane compound having a specific silane compound. By using a resin composition containing the specific silane compound, it is possible to improve the curing characteristics of the compound and form a molded product that not only has an excellent balance between strength and elastic modulus at high temperatures, but also has excellent voltage resistance.
[0029] In this specification, the term "polyfunctional silane compound" includes a silane compound having two or more alkoxysilyl groups and two or more reactive functional groups in one molecule, and the term "monofunctional silane compound" includes a silane compound having one alkoxysilyl group and one reactive functional group in one molecule. The term "reactive functional group" does not include an alkoxy group. Examples of the alkoxy group include a methoxy group, an ethoxy group, and a propoxy group. Examples of the reactive functional group include a (meth)acryloyl group, a vinyl group, an epoxy group, an amino group, an isocyanate group, and a mercapto group.
[0030] From the viewpoint of further improving the curing properties of the compound, the polyfunctional silane compound may have two or more functional groups selected from the group consisting of (meth)acryloyl groups, vinyl groups, epoxy groups, amino groups, isocyanate groups, and mercapto groups, and preferably has two or more functional groups selected from the group consisting of (meth)acryloyl groups, epoxy groups, and mercapto groups. The number of functional groups in the polyfunctional silane compound may be, for example, 2 to 10, 3 to 8, or 4 to 6. The polyfunctional silane compound may be used alone or in combination.
[0031] From the viewpoint of further improving the balance between strength and elastic modulus at high temperatures, the molecular weight of the polyfunctional silane compound may be 500 or more, 600 or more, or 800 or more, and may be 2500 or less, 2000 or less, 1800 or less, or 1500 or less.
[0032] The kinetic viscosity of the polyfunctional silane compound at 25°C is set to 11 mm 2 / s or more, 12mm 2 / s or more, or 13 mm 2 / s or more, 1800 mm 2 / s or less, 1700mm 2 / s or less, or 1600 mm 2 The kinematic viscosity can be measured, for example, using a rheometer in accordance with JIS Z 8803:2011.
[0033] From the viewpoint of further improving voltage resistance, the content of the polyfunctional silane compound may be 1.0 part by mass or more and 20 parts by mass or less, preferably 1.0 part by mass or more and 15 parts by mass or less, more preferably 1.5 parts by mass or more and 10 parts by mass or less, and even more preferably 2.0 parts by mass or more and 7.0 parts by mass or less, relative to 100 parts by mass of the epoxy resin.
[0034] The coupling agent according to the present embodiment may further include a monofunctional silane compound. Examples of the monofunctional silane compound include silane compounds having a (meth)acryloyl group, a vinyl group, an epoxy group, an amino group, an isocyanate group, or a mercapto group. The monofunctional silane compound may be, for example, a silane compound having a mercapto group. Examples of the silane coupling agent having a mercapto group include 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane.
[0035] From the viewpoint of further increasing the mechanical strength of the molded body, the content of the monofunctional silane compound may be 0.1 parts by mass or more and 6.0 parts by mass or less, 0.5 parts by mass or more and 5.0 parts by mass or less, or 1.0 parts by mass or more and 4.0 parts by mass or less, relative to 100 parts by mass of the epoxy resin.
[0036] The resin composition may further contain a curing accelerator (catalyst) to improve the moldability and releasability of the compound. When the resin composition contains a curing accelerator, the mechanical strength of a molded body (e.g., electronic parts) produced using the compound is improved, and the storage stability of the compound in a high temperature and high humidity environment is improved. The curing accelerator is not limited as long as it is a composition that reacts with an epoxy resin to promote the curing of the epoxy resin. The curing accelerator may be, for example, a phosphorus-based curing accelerator, an imidazole-based curing accelerator, or a urea-based curing accelerator.
[0037] Examples of the phosphorus-based curing accelerator include phosphine compounds and phosphonium salt compounds.
[0038] Commercially available imidazole curing accelerators include, for example, 2MZ-H, C11Z, C17Z, 1,2DMZ, 2E4MZ, 2PZ-PW, 2P4MZ, 1B2MZ, 1B2PZ, 2MZ-CN, C11Z-CN, 2E4MZ-CN, 2PZ-CN, C11Z-CNS, 2P4MHZ, TPZ, and SFZ (all of which are product names manufactured by Shikoku Chemical Industry Co., Ltd.).
[0039] The urea-based curing accelerator is not particularly limited as long as it is a curing accelerator having a urea group, but from the viewpoint of improving storage stability, it is preferable to use an alkylurea-based curing accelerator having an alkylurea group. Examples of the alkylurea-based curing accelerator having an alkylurea group include aromatic alkylurea and aliphatic alkylurea. Examples of commercially available alkylurea-based curing accelerators include U-CAT3512T (trade name, manufactured by San-Apro Co., Ltd., aromatic dimethylurea) and U-CAT3513N (trade name, manufactured by San-Apro Co., Ltd., aliphatic dimethylurea). Among these, aromatic alkylurea is preferable because it has a moderately low cleavage temperature and is easy to efficiently cure the compound.
[0040] The amount of the curing accelerator is not particularly limited as long as it is an amount that can obtain a curing acceleration effect. From the viewpoint of improving the curability and flowability of the resin composition when absorbing moisture, the amount of the curing accelerator may be 0.1 parts by mass or more and 20 parts by mass or less, 1 part by mass or more and 15 parts by mass or less, or 2 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the epoxy resin. When the amount of the curing accelerator is 0.1 parts by mass or more, a sufficient curing acceleration effect is easily obtained. When the amount of the curing accelerator is 30 parts by mass or less, the storage stability of the compound is not easily reduced.
[0041] When a molded body is formed from the compound using a mold, the resin composition may contain a wax. The wax increases the fluidity of the compound during molding (e.g., transfer molding) of the compound and also functions as a mold release agent. The wax may be at least one of a fatty acid such as a higher fatty acid and a fatty acid ester.
[0042] Examples of the wax include fatty acids such as montanic acid, stearic acid, 12-oxystearic acid, and lauric acid, and esters thereof; fatty acid salts such as zinc stearate, calcium stearate, barium stearate, aluminum stearate, magnesium stearate, calcium laurate, zinc linoleate, calcium ricinoleate, and zinc 2-ethylhexanoate; and fatty acid salts such as stearic acid amide, oleic acid amide, erucic acid amide, behenic acid amide, palmitic acid amide, lauric acid amide, hydroxystearic acid amide, methylene bisstearic acid amide, ethylene bisstearic acid amide, ethylene bislauric acid amide, distearyl adipate amide, ethylene bisoleic acid amide, dioleyl adipate amide, N-stearyl stearic acid amide. fatty acid esters such as butyl stearate; alcohols such as ethylene glycol and stearyl alcohol; polyethers such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol and modified products thereof; polysiloxanes such as silicone oil and silicone grease; fluorine compounds such as fluorine-based oil, fluorine-based grease, and fluorine-containing resin powder; and waxes such as paraffin wax, polyethylene wax, amide wax, polypropylene wax, ester wax, carnauba wax, and microwax.
[0043] For the purpose of improving the environmental safety, recyclability, moldability, and low cost of the compound, the compound may contain a flame retardant. The flame retardant may be, for example, at least one selected from the group consisting of bromine-based flame retardants, phosphorus-based flame retardants, hydrated metal compound-based flame retardants, silicone-based flame retardants, nitrogen-containing compounds, hindered amine compounds, organometallic compounds, and aromatic engineering plastics. The resin composition may contain one of the above flame retardants, or may contain multiple of the above flame retardants.
[0044] (metal powder) The metal powder (metal element-containing particle) may contain at least one selected from the group consisting of, for example, a metal element, an alloy, and a metal compound. The metal element-containing powder may be, for example, at least one selected from the group consisting of a metal element, an alloy, and a metal compound. The alloy may contain at least one selected from the group consisting of a solid solution, a eutectic, and an intermetallic compound. The alloy may be, for example, stainless steel (Fe-Cr alloy, Fe-Ni-Cr alloy, etc.). The metal compound may be, for example, an oxide such as ferrite. The metal powder may contain one type of metal element or multiple types of metal elements. The metal element contained in the metal powder may be, for example, a base metal element, a precious metal element, a transition metal element, or a rare earth element. The compound may contain one type of metal element-containing powder, or may contain multiple types of metal element-containing powders with different compositions.
[0045] The metal element contained in the metal powder may be at least one selected from the group consisting of iron (Fe), copper (Cu), titanium (Ti), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), tin (Sn), chromium (Cr), niobium (Nb), barium (Ba), strontium (Sr), lead (Pb), silver (Ag), praseodymium (Pr), neodymium (Nd), samarium (Sm) and dysprosium (Dy). The metal powder may further contain elements other than the metal element. The metal powder may contain, for example, carbon (C), oxygen (O), beryllium (Be), phosphorus (P), sulfur (S), boron (B), or silicon (Si).
[0046] The metal powder may be a magnetic powder. The metal powder may be a soft magnetic alloy or a ferromagnetic alloy. The metal powder may be, for example, a magnetic powder made of at least one selected from the group consisting of Fe-Si alloys, Fe-Si-Al alloys (Sendust), Fe-Ni alloys (Permalloy), Fe-Cu-Ni alloys (Permalloy), Fe-Co alloys (Permendur), Fe-Cr-Si alloys (electromagnetic stainless steel), Nd-Fe-B alloys (rare earth magnets), Sm-Fe-N alloys (rare earth magnets), Al-Ni-Co alloys (Alnico magnets), and ferrite. The ferrite may be, for example, spinel ferrite, hexagonal ferrite, or garnet ferrite. The metal powder may be a copper alloy such as a Cu-Sn alloy, a Cu-Sn-P alloy, a Cu-Ni alloy, or a Cu-Be alloy. The metal powder may include one of the above elements and compositions, or may include more than one of the above elements and compositions.
[0047] The metal powder may be Fe simple substance. The metal powder may be an alloy containing iron (Fe-based alloy). The Fe-based alloy may be, for example, an Fe-Si-Cr-based alloy or an Nd-Fe-B-based alloy. The metal element-containing powder may be at least one of an amorphous iron powder and a carbonyl iron powder. When the metal powder contains at least one of Fe simple substance and an Fe-based alloy, it is easy to produce a compact having a high space factor and excellent magnetic properties from the compound. The metal powder may be an Fe amorphous alloy.
[0048] Commercially available Fe amorphous alloy powders include, for example, AW2-08, KUAMET-6B2 (all of which are product names manufactured by Epson Atmix Corporation), DAP MS3, DAP MS7, DAP MSA10, DAP PB, DAP PC, DAP MKV49, DAP 410L, DAP 430L, DAP HYB series (all of which are product names manufactured by Daido Steel Co., Ltd.), MH45D, MH28D, MH25D, and MH20D (all of which are product names manufactured by Kobe Steel, Ltd.).
[0049] <Compound manufacturing method> In the manufacture of the compound, the metal powder and the resin composition (each component constituting the resin composition) are mixed while being heated. For example, the metal powder and the resin composition may be kneaded with a kneader, roll, stirrer, etc. while being heated. By heating and mixing the metal powder and the resin composition, the resin composition adheres to a part or the whole of the surface of the metal element-containing particles constituting the metal powder to cover the metal element-containing particles, and a part or the whole of the epoxy resin in the resin composition becomes a semi-cured product. As a result, a compound is obtained. The compound may be obtained by further adding wax to the powder obtained by heating and mixing the metal powder and the resin composition. The resin composition and the wax may be mixed in advance.
[0050] In the kneading, the metal powder, the epoxy resin, the curing agent, the curing accelerator, and the coupling agent may be kneaded in a tank. After the metal powder and the coupling agent are charged into the tank and mixed, the epoxy resin, the curing agent, and the curing accelerator may be charged into the tank to knead the raw materials in the tank. After the epoxy resin, the curing agent, and the coupling agent are kneaded in the tank, the curing accelerator may be charged into the tank to further knead the raw materials in the tank. A mixed powder (resin mixed powder) of the epoxy resin, the curing agent, and the curing accelerator may be prepared in advance, and then the metal powder and the coupling agent may be kneaded to prepare the metal mixed powder, and then the metal mixed powder and the above-mentioned resin mixed powder may be kneaded.
[0051] The kneading time depends on the type of kneading machine, the volume of the kneading machine, and the amount of compound produced, but is preferably 1 minute or more, more preferably 2 minutes or more, and even more preferably 3 minutes or more. The kneading time is preferably 20 minutes or less, more preferably 15 minutes or less, and even more preferably 10 minutes or less. If the kneading time is less than 1 minute, the kneading is insufficient, the moldability of the compound is impaired, and the degree of hardening of the compound varies. If the kneading time exceeds 20 minutes, for example, the hardening of the resin composition (e.g., epoxy resin and phenol resin) progresses in the tank, and the fluidity and moldability of the compound are easily impaired.
[0052] When the raw materials in the tank are kneaded with a kneader while being heated, the heating temperature may be, for example, a temperature at which a semi-cured epoxy resin (B-stage epoxy resin) is produced and the production of a cured epoxy resin (C-stage epoxy resin) is suppressed. The heating temperature may be a temperature lower than the activation temperature of the curing accelerator. The heating temperature is, for example, preferably 50°C or higher, more preferably 60°C or higher, and even more preferably 70°C or higher. The heating temperature is preferably 150°C or lower, more preferably 120°C or lower, and even more preferably 110°C or lower. When the heating temperature is within the above range, the resin composition in the tank is softened and easily covers the surface of the metal element-containing particles constituting the metal powder, a semi-cured epoxy resin is easily produced, and complete curing of the epoxy resin during kneading is easily suppressed.
[0053] [Molded body] The molded article according to the present embodiment may include the above-mentioned compound. The molded article according to the present embodiment may include a cured product of the above-mentioned compound. The molded article may include at least one selected from the group consisting of an uncured resin composition, a semi-cured product of the resin composition (B-stage resin composition), and a cured product of the resin composition (C-stage resin composition). The molded article according to the present embodiment may be used as a sealant for electronic components or electronic circuit boards. According to the present embodiment, cracks in the molded article caused by the difference in thermal expansion coefficient between the metal member of the electronic component or electronic circuit board and the molded article (sealant) can be suppressed.
[0054] The cured product of the compound is a cured product of the metal powder and the resin composition. The bending strength of the cured product at 250°C may be 4.0 MPa or more, 4.5 MPa or more, or 4.8 MPa or more from the viewpoint of increasing the strength of the cured product. The upper limit of the bending strength is about 10 MPa. The bending modulus of the cured product at 250°C may be 1.3 GPa or less, 1.2 GPa or less, or 1.1 GPa or less from the viewpoint of imparting flexibility to the cured product. The lower limit of the bending modulus is about 0.1 GPa. The value obtained by dividing the bending strength (MPa) at 250°C by the bending modulus (GPa) at 250°C can be used as an index of the reliability of the cured product. The index is 7.3×10 -3 More preferably, it is 7.5×10 -3 More preferably, it is 7.8×10 or more. -3 The upper limit of the index is not particularly limited, and is, for example, 5×10 -2 It may be the following.
[0055] <Method of manufacturing molded body> The method for producing a molded body according to the present embodiment may include a step of pressurizing the compound in a mold. The method for producing a molded body may include a step of pressurizing the compound covering a part or the entire surface of the metal member in a mold. The method for producing a molded body may include only the step of pressurizing the compound in a mold, or may include other steps in addition to the step. The method for producing a molded body may include a first step, a second step, and a third step. Each step will be described in detail below.
[0056] In the first step, a compound is prepared by the method described above.
[0057] In the second step, the compound is pressed in a mold to obtain a molded body (B-stage molded body). In the second step, the compound covering a part or the whole surface of the metal member may be pressed in a mold to obtain a molded body (B-stage molded body). In the second step, the resin composition is filled between the individual metal element-containing particles constituting the metal element-containing powder. The resin composition functions as a binding material (binder) to bind the metal element-containing particles to each other.
[0058] In the second step, transfer molding of the compound may be performed. In the transfer molding, the compound may be pressurized at 5 MPa or more and 50 MPa or less. The higher the molding pressure, the easier it is to obtain a molded body with excellent mechanical strength. In consideration of the mass productivity of the molded body and the life of the mold, the molding pressure is preferably 8 MPa or more and 20 MPa or less. The density of the molded body formed by transfer molding may be preferably 75% or more and 86% or less, more preferably 80% or more and 86% or less, based on the true density of the compound. When the density of the molded body is 75% or more and 86% or less, a molded body with excellent mechanical strength is easily obtained. In the transfer molding, the second step and the third step may be performed at the same time.
[0059] In the third step, the molded body is cured by heat treatment to obtain a molded body in the C stage. The heat treatment temperature may be any temperature at which the resin composition in the molded body is sufficiently cured. The heat treatment temperature may be preferably 100°C or more and 300°C or less, more preferably 110°C or more and 250°C or less. In order to suppress oxidation of the metal powder in the molded body, it is preferable to perform the heat treatment in an inert atmosphere. When the heat treatment temperature exceeds 300°C, the metal powder is oxidized or the resin cured product is deteriorated by a trace amount of oxygen inevitably contained in the heat treatment atmosphere. In order to sufficiently cure the resin composition while suppressing oxidation of the metal powder and deterioration of the resin cured product, the heat treatment temperature may be held for preferably several minutes or more and 10 hours or less, more preferably 3 minutes or more and 8 hours or less. EXAMPLES
[0060] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0061] Details of each component used in preparing the compounds of the Examples and Reference Examples are given below.
[0062] (Epoxy resin) Biphenylene aralkyl type epoxy resin (product name: NC-3000, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 275g / eq) Multifunctional epoxy resin (Product name: TECHMORE VG-3101L, manufactured by Printec Co., Ltd., epoxy equivalent: 215g / eq) (hardening agent) Phenol novolac resin (product name: HF-3M, manufactured by Meiwa Kasei Co., Ltd.)
[0063] (Coupling Agent) A polyfunctional silane compound having a mercapto group (trade name: X-12-1154, manufactured by Shin-Etsu Chemical Co., Ltd., kinematic viscosity (25°C): 1460 mm 2 / s) Polyfunctional silane compound having an epoxy group (trade name: KR-517, manufactured by Shin-Etsu Chemical Co., Ltd., kinematic viscosity (25°C): 14.7 mm 2 / s) Multifunctional silane compound having an acryloyl group (trade name: KR-513, manufactured by Shin-Etsu Chemical Co., Ltd., kinematic viscosity (25°C): 40 mm 2 / s) 3-Glycidoxypropyltrimethoxysilane (trade name: KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd., kinematic viscosity (25°C): 3.05 mm 2 / s) 3-Mercaptopropyltrimethoxysilane (trade name: KBM-803, manufactured by Shin-Etsu Chemical Co., Ltd., kinematic viscosity (25°C): 1.36 mm 2 / s)
[0064] (Cure accelerator) Aromatic dimethylurea (product name: U-CAT3512T, manufactured by San-Apro Co., Ltd.) (Release agent) Partially saponified Montan acid ester wax (product name: LICOWAX-OP, manufactured by Clariant Chemicals Co., Ltd.)
[0065] (metal powder) Amorphous iron powder (Epson Atmix Corporation product name: 9A4-II, average particle size 24 μm) FeSiCr alloy powder (manufactured by Shinto Kogyo Co., Ltd., average particle size: 2.1 μm)
[0066] [Preparation of compound] (Examples 1 to 5) The epoxy resin, curing agent, curing accelerator, and release agent shown in Table 1 were placed in a plastic container in the amounts (unit: g) shown in the same table. These materials were mixed in the plastic container for 10 minutes to prepare a resin mixture. The resin mixture corresponds to all components of the resin composition except for the coupling agent.
[0067] Amorphous iron powder and FeSiCr alloy powder (mass ratio 82:18) were mixed uniformly for 5 minutes in a pressurized twin-axis kneader (manufactured by Nippon Spindle Manufacturing Co., Ltd., capacity 5 L) to prepare a metal powder. The coupling agent shown in Table 1 was added to the metal powder in the twin-axis kneader. Then, the contents of the twin-axis kneader were heated to 90°C, and the contents of the twin-axis kneader were mixed for 10 minutes while maintaining the temperature. Then, the above resin mixture was added to the contents of the twin-axis kneader, and the contents were melted and kneaded for 15 minutes while maintaining the temperature of the contents at 120°C. The kneaded product obtained by the above melting and kneading was cooled to room temperature, and then crushed with a hammer until the kneaded product had a predetermined particle size. The above "melt" means that at least a part of the resin composition in the contents of the twin-axis kneader is melted. The metal powder in the compound does not melt during the preparation process of the compound. The compounds of Examples 1 to 5 were prepared by the above method.
[0068] (Comparative Examples 1 to 3) The compounds of Comparative Examples 1 to 3 were prepared in the same manner as in the Examples, except that the types and amounts of each component were changed as shown in Table 2.
[0069] [Compound evaluation] The compounds obtained in the Examples and Reference Examples were evaluated as follows. The results are shown in Tables 1 and 2.
[0070] (Bending test) The compound was transfer molded under the conditions of a mold temperature of 175°C, a molding pressure of 13.5 MPa, and a curing time of 360 seconds, and then post-cured at 180°C for 6 hours to obtain a test specimen. The dimensions of the test specimen were 80 mm long x 10 mm wide x 3.0 mm thick.
[0071] A three-point support bending test was carried out on the test specimen at 250°C using an autograph with a thermostatic chamber. The autograph used was an AGS-500A manufactured by Shimadzu Corporation. In the bending test, one side of the test specimen was supported by two supports. A load was applied to the center position between the two supports on the other side of the test specimen. The load at which the test specimen broke was measured. The measurement conditions for the bending test were as follows: Distance between two supports Lv: 64.0±0.5mm Head speed: 2.0±0.2mm / min Chart speed: 100mm / min Chart full scale: 490N (50kgf)
[0072] The bending strength σ (unit: MPa) was calculated based on the following formula (A). The bending modulus E (unit: GPa) was calculated based on the following formula (B). In the formulas below, "P" is the load (unit: N) when the test piece breaks. "Lv" is the distance between two supports (unit: mm). "W" is the width of the test piece (unit: mm). "t" is the thickness of the test piece (unit: mm). "F / Y" is the gradient of the straight line portion of the load-deflection curve (unit: N / mm). σ = (3 × P × Lv) / (2 × W × t 2 ) (A) E=[Lv 3 / (4×W×t 3 )]×(F / Y) (B)
[0073] (Reliability) The reliability evaluation index was determined by dividing the bending strength (MGa) at 250° C. by the bending modulus (GPa) at 250° C. The larger this value, the better the balance between strength and modulus.
[0074] (Voltage resistance) The compound was transfer molded under the conditions of a mold temperature of 175°C, molding pressure of 13.5MPa, and curing time of 360 seconds, and then post-cured at 180°C for 6 hours to prepare a test specimen with a thickness of 2.0 mm. For the voltage resistance test, a stainless steel plate connected to a ground wire, a conductive rubber plate, a test specimen, and a stainless steel electrode with a diameter of 10 mm connected to a high-voltage wire were arranged on an insulating plate in this order. The high-voltage wire and the ground wire were connected to the high-voltage output terminal and the ground terminal of a high-voltage amplifier, respectively. The waveform output of the function generator was input to the high-voltage amplifier, and a test voltage was generated so that it increased from 0V to a maximum of 2000V at a rate of 10V per second, and applied to the test specimen. The voltage was read when the current passing through the test specimen exceeded 10mA. Next, stainless steel electrodes were placed at different positions on the test specimen, and voltage was applied in the same manner. The test was repeated 14 times, and the median value of the voltage readings was taken as the voltage resistance (dielectric breakdown voltage: V / mm) of the test specimen.
[0075] [Table 1]
[0076] [Table 2]
[0077] The compound according to the present invention is capable of forming a molded article that has an excellent balance between strength and elastic modulus at high temperatures and has excellent voltage resistance.
Claims
1. The present invention comprises a metal powder and a resin composition containing an epoxy resin, a curing agent, and a coupling agent, The coupling agent has a kinetic viscosity at 25° C. of 10 to 2000 mm 2 / s, The compound has a content of the polyfunctional silane compound of 1.0 part by mass or more and 20 parts by mass or less relative to 100 parts by mass of the epoxy resin.
2. The compound according to claim 1, wherein the polyfunctional silane compound has two or more functional groups selected from the group consisting of a (meth)acryloyl group, a vinyl group, an epoxy group, an amino group, an isocyanate group, and a mercapto group.
3. The compound according to claim 1 or 2, wherein the content of the metal powder is 90% by mass or more and less than 100% by mass.
4. A molded body comprising the compound according to any one of claims 1 to 3.
5. A cured product of the compound according to any one of claims 1 to 3.
Citation Information
Patent Citations
Method for producing silicone oligomer
JP2007326848A
inductor
JP2014013803A
Bond magnet hardened body
JP2017073479A
Metal element-containing powder, and molded body
JP2019104954A
Compound powder
WO2019167182A1